Lamotrigine Reduces the Number of Vertigo Attacks in Patients with Meniere’s Disease: A Pilot Study - Zhang, MD, PhD*, Lixin; Sanders, PhD, D. Merika W.; So, MSc, Jamie Y.; Zhang, MD, Clark; Stephenson, BS, Karen M.; Cox, PhD, Jennifer L.; Pearson, MS, Hailley A. (North American Journal of Medicine and Science, 2024)
Spontaneous episodes of vertigo, called vertigo attacks, are the most disabling symptom of Meniere’s disease (MD). The purpose of this study was to compare the number vertigo attacks in patients with MD before and after establishing a maintenance dose of lamotrigine (Lamictal ®). A retrospective chart review was conducted on patients who were diagnosed with definite, unilateral MD, and prescribed lamotrigine for potential management of MD vertigo attacks. Patients were divided into two groups based on whether they had a history of migraine because migraine is one factor that distinguishes MD clinical subgroups. The number of vertigo attacks experienced by each patient was retrieved from clinic visit notes. The number of vertigo attacks in the 12 weeks prior to prescription of lamotrigine (Baseline) and in the first 12 weeks on a maintenance dose of lamotrigine (Maintenance) were compared via paired t-tests within the groups. Overall, thir-ty-three patients met criteria, of which 13 had and 20 did not have history of migraine. The number of attacks reported during Maintenance was significantly less than that reported during Baseline both for patients with (p = 0.001) and without (p = 0.0005) history of migraine. Both MD patients with and without migraine reported fewer vertigo attacks while on a maintenance dose of lamotrigine than prior to prescription of lamotrigine. [N A J Med Sci. 2024;17(1):008-010. DOI: 10.7156/najms.2024.1701008] Key Words: Lamictal, episodic dizziness, endolymphatic hydrops, vestibular migraine, migraine-associated vertigo, vestibular disorders, hearing loss, tinnitus